Functional exhaustion of CD4+T cells in HIV/HCV coinfected HAART-treated patients - V. V. Vlasova; L. B. Korolevskaya; O. A. Loginova; N. G. Shmagel; E. V. Saidakova (Медицинская иммунология)
Infection with hepatitis C virus (HCV) is common among HIV-positive patients, with up to 50% of them being coinfected in Russia. While highly active antiretroviral therapy (HAART) suppresses HIV replication and restores the immune system of HIV-infected subjects, HCV coinfection interferes with CD4+T cell regeneration and increases the risk of patients’ morbidity and mortality. During HAART, HIVinfection progression and the immune system restoration efficiency largely depend on immune activation and CD4+T cell exhaustion. This study determined the level of activation, exhaustion, and cytokine production in CD4+T cells obtained from the peripheral blood of HAART-treated HIV/HCV coinfected and HIV monoinfected subjects. The study comprised 11 HIV/HCV coinfected individuals and 10 HIV monoinfected patients receiving HAART for more than two years, with a control group of 10 volunteers without the signs of HIV or HCV infections. Compared with healthy controls, HIV/HCV coinfected patients had an increased frequency of activated CD38+HLA-DR+ CD4+T lymphocytes (p < 0.05), a higher level of CD4+T cell exhaustion determined according to the TIGIT expression density per cell (p < 0.05), and a greater proportion of interferon-gamma (IFNγ)-producing CD4+T lymphocytes following activation (p < 0.05). The frequency of IFNγ-producing CD4+T cells in the donors’ blood positively correlated with the proportion of activated CD4+T cells (R = 0.514, p < 0.01). Despite having a large number of IFNγ-producing CD4+T lymphocytes, the HIV/HCV coinfected patients’ average production of IFNγ by CD4+T cells was significantly lower than that in healthy controls (p < 0.05). The IFNγ production in CD4+T lymphocytes did not depend on activation (p > 0.05). However, a negative correlation was established between the IFNγ production and the level of CD4+T cell exhaustion (R = -0.400, p < 0.05). The letter was also found to inversely correlate with the CD4+T cell counts in the donors’ peripheral blood (R = -0.598, p < 0.01). These data suggest that HCV coinfection leads to pronounced functional exhaustion of CD4+T cells and may aggravate the course of HIVinfection in patients receiving HAART.